Paradoks Dwi Fungsi Pajak Antara Beban atau Manfaat? Indonesia - ., muaimin (Jurnal Aplikasi Perpajakan, 2024)
This research discusses the dualism of the role of taxes as a burden or benefit for society from a public economic perspective. Using a literature study approach, this research analyzes various sources to explore the contradiction between tax as an obligation that burdens taxpayers and tax as an important instrument in financing state development. The study results show that taxes, although often considered a burden because they reduce taxpayers' income, have a major contribution in funding infrastructure, education, health and income redistribution programs. These findings provide a deeper understanding of how tax policies can be designed to achieve a balance between maximizing state revenues and minimizing the burden on taxpayers, as well as providing recommendations for policies that are more effective and fair in supporting community welfare.